One-step preparation of Hageman factor fragment concentrate - Simonianová, E (Biomedical chromatography, 1992)
The Hageman factor fragment (HFf) concentrate was prepared from acetone and dextran sulphate activated human plasma by chromatography on a CM-Sephadex column. The preparation was free of the main kallikrein inhibitors--Cl-inactivator, alpha 2-macroglobulin, antithrombin III and alpha 1-antitrypsin. The HFf concentrate can serve as an activator of prekallikrein in patient plasma.
Keywords: Peptide Fragments; Blood; Enzyme Activation; Prekallikrein; prekalikrein; Humans; Chromatography, Liquid; peptidové fragmenty; Factor XII; chromatografie kapalinová; faktor XII; lidé; krev; aktivace enzymů